Laquinimod Protects Against TNF-α-Induced Attachment of Monocytes to Human Aortic Endothelial Cells (HAECs) by Increasing the Expression of KLF2 - Jiang T; Zhang W; Wang Z (Dove Medical Press, 2020)
Tiechao Jiang, 1– 3 Wenhao Zhang, 1 Zhongyu Wang 1– 3 1Department of Cardiovascular Medicine, The Third Hospital of Jilin University, Changchun 130033, People’s Republic of China; 2Jilin Provincial Precision Medicine Key Laboratory for Cardiovascular Genetic Diagnosis, China-Japan Union Hospital of Jilin University, Changchun 130033, People’s Republic of China; 3Jilin Provincial Engineering Laboratory for Endothelial Function and Genetic Diagnosis of Cardiovascular Disease, The Third Hospital of Jilin University, Changchun 130033, People’s Republic of ChinaCorrespondence: Zhongyu WangDepartment of Cardiovascular Medicine, The Third Hospital of Jilin University, No. 126, Xiantai Street, Changchun 130033, People’s Republic of ChinaTel +86-431-84995258Email jldxwzy@jlu.edu.cnIntroduction: As a worldwide health issue, the treatment and prevention of atherosclerosis present an important goal. Increased levels of proinflammatory cytokines such as TNF-α-associated chronic inflammatory response cause endothelial cells to lose their ability to regulate vascular function. Lipid-laden immune cells are recruited to the endothelium where they adhere to the endothelial wall and invade the intimal space, thereby leading to the development of atherosclerotic lesions, fatty plaques, and thickening of the arterial wall. In the present study, for the first time, we investigated the effects of laquinimod, an immunomodulatory agent used for the treatment of multiple sclerosis, on human aortic endothelial in a TNF-α-induced atherosclerotic microenvironment. At present, the mechanism of action of laquinimod is not well defined.Methods: The effects of laquinimod on the gene expression of IL-6, MCP-1, VCAM-1, E-selectin, and KLF2 were measured by real-time PCR. ELISA assay was used to determine protein secretion and expression. Phosphorylation of ERK5 and the protein level of KLF2 were measured by Western blot analysis. The attachment of monocytes to endothelial cells was assayed by calcein-AM staining and fluorescent microscopy.Results: Our findings demonstrate that laquinimod reduced the expression of key inflammatory cytokines and chemokines, including IL-6, MCP-1, and HMGB1. We further demonstrate that laquinimod significantly reduced the attachment of monocytes to endothelial cells, which is mediated through reduced expression of the cellular adhesion molecules VCAM-1 and E-selectin. Here, we found that laquinimod could significantly increase the expression of KLF2 through activation of ERK5 signaling. The results of our KLF2 knockdown experiment confirm that the effects of laquinimod observed in vitro are dependent on KLF2 expression.Conclusion: Together, these findings suggest a potential antiatherosclerotic capacity of laquinimod. Further research will elucidate the underlying mechanisms.Keywords: atherosclerosis, laquinimod, endothelial cells, TNF-α, VCAM-1, E-selectin, KLF2